Chitin-acetate/DMSO as a supramolecular green CO2-phile. Issue 26 (23rd February 2016) - Eftaiha, Ala'a F.; Alsoubani, Fatima; Assaf, Khaleel I.; Nau, Werner M.; Troll, Carsten; Qaroush, Abdussalam K.
Abstract : The supramolecular chemisorption of CO2 by the oligosaccharide chitin-acetate (CA) in DMSO as a green, binary sorbent-based system offers a potential, novel and eco-friendly approach for post combustion capture applications. Abstract : The supramolecular chemisorption of CO2 by the oligomeric chitin-acetate (CA) in DMSO as a green solvent offers a novel eco-friendly approach for CO2 capture. Since the amino groups in the sorbent material are blocked either by protonation or acetylation, the multi-armed hydroxyl based oligosaccharide captures CO2 through the formation of an organic carbonate species as confirmed by 13 C NMR, in situ ATR-FTIR spectroscopy and conductivity. DFT calculations verified the formation of the CA-CO2 adduct, in which the organic carbonate group is stabilized through supramolecular ionic interaction and hydrogen bonding with the neighboring ammonium ion and hydroxyl functional group along the oligomer backbone. The use of other polar aprotic solvents ( N, N -dimethylformamide (DMF), acetonitrile, and acetone) was not successful due to solubility issues.